2013
DOI: 10.1093/trstmh/trs090
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characteristics and biofilm formation among Escherichia coli isolates from Indian women with acute cystitis

Abstract: Distribution of virulence genotypes and phylotypes can vary with geographical location and the isolates from western countries cannot be treated as prototypes for Asian cystitis isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
4
8
1
Order By: Relevance
“…It is believed that hly is more common among invasive uropathogenic strains than in nonpathogenic or commensal isolates of E. coli (38). In the present study, 77% of the hly genes were detected in phylogroups B 2 and D. This confirms the results of previous research showing that these phylogroups are more pathogenic and have more virulence factors than others, although different studies have shown the prevalence of hly in UPEC isolates to range from 2% to 47% in different countries (10,39,40).…”
Section: Discussionsupporting
confidence: 92%
“…It is believed that hly is more common among invasive uropathogenic strains than in nonpathogenic or commensal isolates of E. coli (38). In the present study, 77% of the hly genes were detected in phylogroups B 2 and D. This confirms the results of previous research showing that these phylogroups are more pathogenic and have more virulence factors than others, although different studies have shown the prevalence of hly in UPEC isolates to range from 2% to 47% in different countries (10,39,40).…”
Section: Discussionsupporting
confidence: 92%
“…Biofilm production allows bacteria to persist in the host and can be associated with the gravity of the infection (Høiby et al, 2011 ). UPEC strains have been shown to present varying levels of biofilm production (Watts et al, 2010 ; Novais et al, 2012 ; Ponnusamy et al, 2012 ; Agarwal et al, 2013 ; Tapiainen et al, 2014 ; Flament-Simon et al, 2019 ). Herein, we showed that UPEC 252 is not capable of producing biofilm on abiotic surfaces under the conditions tested.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PapG II variant gene from MDR- and XDR-UPEC strains associated with phylogenetic groups D and B2 was the most prevalent compared to the papG I and papG III variant genes. The papG II variant gene from UPEC strains associated with phylogenetic groups A and B2 is the most prevalent gene associated with cystitis in women and pyelonephritis in children and adults (Jantunen et al, 2000; Agarwal et al, 2013). However, four MDR-UPEC strains associated with phylogenetic group B2 and one strain associated with group D were associated with the papG III variant gene, which correlates with data reported by other authors (Agarwal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%